PENGARUH WHISTLEBLOWING, DAN SKEPTISME PROFESIONAL TERHADAP PENDETEKSIAN KECURANGAN DENGAN RED FLAGS SEBAGAI PEMODERASI - Susi Sih Kusumawardhany; Yunita Kurnia Shanti (ITB AAS Indonesia Surakarta, 2026)
This study aims to examine and obtain evidence regarding the influence of whistleblowing and professional skepticism on fraud detection, moderated by red flags, among auditors at the Inspectorate General of the Ministry of Education and Culture, Region IV, Central Jakarta. This quantitative study used primary data in the form of questionnaires distributed to respondents. The sample selection method used saturated sampling, resulting in 75 respondents and and 57 respondents were obtained as a sample that could be processed. Data analysis used SPSS version 24 along with the MRA test. Based on the data analysis, the results indicate that whistleblowing has no effect on fraud detection, and professional skepticism has effect on fraud detection. The MRA test results indicate, first, that red flags are unable to moderate the effect of whistleblowing on fraud detection, and second, that red flags are able to moderate the effect of professional skepticism on fraud detection.